ENZYMATIC MONITORIZATION OF MURAL PAINTINGS BIODETERIORATION - Rosado, Tânia (2014)
Biodeterioration of mural paintings by microorganisms is an important research field that needs novel approaches to fully understand the mechanisms and effects. In this work, the presence of microorganisms and their biological activity were investigated by extra and intracellular enzymatic monitorization. The enzymes arylsulphatase, β-glucosidase, dehydrogenase and phosphatase were used as biomarkers of the microbial metabolic activity, and the viability cellular assays revealed a relationship with the degradation levels of the paintings. In this way, the metabolic activity of the microbial population can be correlated with the contamination levels detected and with biodeterioration status of the paintings. Therefore, enzymatic approaches constitute good biomarkers to be applied in this research field and are useful to detect biodeteriogenic agents.